A certain disconfort populates the territory of geographical education: putting to the test the model of didactic transposition - Roberto Filizola (Universidade Federal de Santa Catarina, 2018)
The knowledges with which students and teachers work in the classroom seem to assume a growing distance between the proposed and the effectively realized, resulting in frustration. Paradoxically, geography is attributed a formative potential that ensures it is highlighted in the group of school subjects, placing it as a field par excellence of multidisciplinarity. Geography establishes an interface with various branches of knowledge and draws attention by dealing with themes and contents that emerge from the physical and social worlds, the material and the ideal. Like a ball of wool, the crisis of the teaching of Geography presents several skeins, capable of hindering innovation or advancement in geographic education. Would the problem lie in the contents? Does your teaching find itself detached from the dimension of a geographically educating? Does the teaching-learning relationship result in knowledge that is minimally appropriate for students? In the present article we propose a reflection about the meetings and disagreements in the geographic education from the problematization of the relation between the school discipline and the university geography. Therefore, we will be using the concepts of school culture and teacher knowledge to support the thesis that a revitalization of geographic education capable of ensuring the formation of critical citizenship must necessarily put to the test the model of didactic transposition in which the School discipline is conceived as a passive receptacle of knowledge produced in the academic field, besides situating the teacher as a mere reproducer of that knowledge.